Comparative hydrometeors measured by a PARSIVEL disdrometer at Tianshan mountains in arid regions of China - Zhao, Chuancheng; Yao, Shuxia; Ding, Yongjian; Zhao, Qiudong; Zhou, Jiaxin (Scientific reports, 2025)
Knowledge of microphysical characteristics of precipitation, including intensity, drop size, fall velocity, and kinetic energy, is crucial for the quantitative measurement of precipitation using radar and for estimating precipitation erosivity. This study investigates the variations in precipitation parameters from August 2019 to August 2021 at a high-altitude site in the Tianshan Mountains, located in the arid regions of China, utilizing an optical disdrometer. Detailed analyses are provided on precipitation intensity ( I ), drop size distribution, fall velocity, radar reflectivity ( Z ), and kinetic energy ( KE ). Additionally, empirical relationships between precipitation intensity and radar reflectivity ( Z-I ) as well as between intensity and kinetic energy ( KE-I ) are established. The proportion of precipitation events with an intensity of less then 2.5 mm h −1 is higher during the dry season compared to the wet season, whereas the proportion of events with an intensity of less than 10 mm h −1 is lower in the wet season. The characteristics of the drop size distribution are consistent with those of intensity. Due to the increased occurrence of solid precipitation (snow) during the dry season, fall velocities are greater in the wet season. The correlation coefficient values for the Z-I relationship are low, whereas the exponent values are high. Furthermore, there is a distinct variation in the coefficient and exponents of the Z-I relationship between the wet and dry seasons. A power-law model for the KE-I relationship is also proposed. The kinetic energy over a 1-minute was calculated using five different KE-I equations, and these results were subsequently compared to assess the model’s performance.